Pengaruh Promosi dan Word of Mouth Terhadap Minat Berkunjung ke Wisata Religi Makam Sunan Giri Gresik - Agitasari, Debora Annisa; Krisnanda, Rulli; Anwar Sani, Fitria Earlike (Jurnal Pariwisata Tourista, 2022)
Religious tourism is a new type of tourism that is being favored by several people, this type of special interest tourism is closely related to pilgrimage tourism, one of which is religious tourism to the tomb of Sunan Giri Gresik. This study aims to determine and analyze the effect of partial and simultaneous promotion and word of mouth on interest in visiting the Religious Tourism of the Sunan Giri Tomb. The population of this study is all people who have never visited or become potential tourists, with a sample of 110 people. The data collection technique in this study used a questionnaire given online to potential tourists. The data analysis technique used in this research is descriptive statistical analysis, multiple linear regression and hypothesis testing. The results showed that promotion did not partially affect the interest in visiting tourists, but promotion and word of mouth simultaneously affected the interest in visiting. The results of further research showed that word of mouth had a dominant effect on visiting interest. With this, it adds to the perspective that the better the role of the community in conveying positive things about a tour, the more interest in visiting tourists.